The Influence of The STEM Learning Approach on Students Communication and Collaboration Abilities on Elasticity Materials - Khoiriyah, Solatun; Wiliyanti, Vandan; Gunawan, Indra (Jurnal Penelitian Pembelajaran Fisika, 2024)
This research aims to determine the influence of the STEM learning approach on students' communication and collaboration abilities in elasticity materials. The type of research is quasi-experimental, with a non-equivalent control group design. The population of this study consists of students from grade XI MIA at MAN 1 Bandar Lampung. We used simple random sampling as the sampling technique, designating XI MIA 3 as the experimental group and XI MIA 4 as the control group. The instruments used are questionnaires and observation sheets. We employ the questionnaire, which uses a Likert scale with five answer options, to measure students' communication and collaboration abilities. We use the observation sheet to assess the implementation process of STEM learning. We conduct data analysis using the t-test with SPSS version 25.0. The research findings indicate that the communication and collaboration abilities of students in the experimental group are higher than those in the control group, with a Sig. (2-tailed) value of 0.000, showing a significant difference in communication and collaboration abilities between students using STEM learning and those using conventional learning. This study concludes that there is a significant influence of the STEM approach on students' communication and collaboration abilities in the subject of elasticity.Â Keywords:Â STEM, Communication, Collaboration, Elasticity